Peran Dakwah Dalam Keluarga Dan Relevansinya Bagi Pembentukan Karakter Anak - Jon Paisal (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2021)
The family is the main person in charge of preaching to shape the character of children to become children who have religious and cultural norms. In research using the library research method (literature) by taking sources from books, journals, and other scientific papers tThe family is the main person in charge of preaching to shape the character of children to become children who have religious and cultural norms. In research using the library research method (literature) by taking sources from books, journals, and other scientific papers that support this research. The research aims to find Islamic law and views on da'wah to the family. The results showed that: Da'wah shapes the character of the child in the family into a priority and obligation for Islam, according to the word of Allah SWT in the Al-Qur'an, Surat Lukaman verse, 13. Then Q.S. Lukman verse 17. And Q.S Lukman verse 18. Furthermore, in Q.S: At-Tahrim. Allah commands humans to protect themselves and their children from the fires of hell. In the history of Islam before Rasulullah SWA broadcast the messages of Islam to the wider community, he preached to his family and close relatives. From this story, a reference to da'wah can be drawn to the family to educate children to become believers, obedient to worship and become children with noble character.